Strategies for Green Economy in China - Alina Steblyanskaya; Mingye Ai; Vladimir Bocharnikov; Artem Denisov (Foresight and STI Governance)
The transition to a “green” economic model is a complex strategic task that requires a combination of two previously incompatible development vectors: maintaining dynamic economic growth and preserving the natural environment on a long-term basis. No country has yet been able to cope with such complexity, nevertheless, an active search for a new balanced model continues, with the development of appropriate strategies. China is among the countries moving in this direction. The article analyzes the influence of social, economic, and environmental factors on the prospects for the development of a green economy and the preservation of natural areas in China. The dynamics of changes in the ecological situation from 1970 to 2018 is investigated. The authors propose a methodology for assessing the state of the environment based on demographic dynamics, economic indicators, and the level of technological development. Over the past 50 years, China has experienced intensive industrial development, as a result of which the degradation of valuable natural assets is increasing in most regions. At the same time, efforts are being made in a number of provinces to remedy the situation through the formulation of new policies, the first results of which have been already visible. The government has established a new environmental legislation designed to scale the green practices of the pioneering regions throughout the country, including the trend toward the de-urbanization of individual megacities and others. The implementation of this strategy will be facilitated by the expansion of interdisciplinary scientific research, the development of complex technological solutions, and development programs that simultaneously take into account various factors.